Rationalization of agriculture activities among selected industrial crops - Mohayidin, Mohd Ghazali; Hussein, Mohd Ariff (1988)
The Malaysian government allocated some M$12 billion to finance the country's agriculture and rural development for the 1986-1990 period. In spite of this huge allocation, the government appears to have no rational means of evaluating the performance of the various government institutions and programs. This paper look into the broad Government agricultural policy, applies some evaluation criteria to gauge performances of several types of smallholder (categorized according to the corresponding public agricultural development agencies) as well as private estates, and attempts to rationalize the agricultural activities of the various groups. A subjective application of the criteria indicates a very wide range of performance standards. The private estates are seen to be performing far better than any of the types of smallholder on almost every count, including poverty alleviation. The results also indiacate the need for a shift towards a more positive adjusment policies with a greater involvement of the private estates in the process of agricultural and export products development.